On LIBERATING EDUCATION AND THE CREATION OF GOLDEN INDONESIA BY 2045 - ajes, editor; Tans, Felix (Academic Journal of Educational Sciences, 2024)
This article focusses on education. Here, the writers argue that liberating education, widely known as “Program Merdeka Belajar” in Indonesia, be used consistently as a means to successfully create golden Indonesia by 2045. To make its implementation more effective, however, the following ideas be seriously taken into account. First, it is necessary to implement an educational system, from primary to tertiary institutions, based on each single student’s talents, interests, and learning needs. Second, in relation to the first, it is urgent that Indonesian Government stops creating a national curriculum to be nationally applied throughout Indonesia; the Government instead allows each educational institute in this country to have its own “Merdeka Belajar Curriculum,” that is, a school curriculum based on each single student’s talents/potentials, interests, and learning needs. It is, therefore, suggested that a curriculum for each educational institution may no longer be created by Jakarta/Nusantara. Third, to implement “Program Merdeka Belajar” successfully, having great teachers who teach based on their students’ talents, interests, and learning needs is necessary. To achieve this, we suggest, among other things, that the teachers be freely allowed to have further education and/or proper training and that their salary be increased significantly. This, in turn, will lead to the successful creation of Golden Indonesia in 2045 and beyond.